Social Gains in the Balance : A Fiscal Policy Challenge for Latin America and the Caribbean - World Bank (Washington, DC, 2014)
In 2012, the Latin America and the Caribbean (LAC) region continued its successful drive to reduce poverty and build the middle class. The proportion of the region's 600 million people living in extreme poverty, defined in the region as life on less than $2.50 a day, was cut in half between 2003 and 2012 to 12.3 percent. Reflecting the upward mobility out of poverty, households vulnerable to falling back into poverty became the largest group in LAC in 2005, and represent almost 38 percent of the population. However, in the last two years, the share of vulnerable households has started to decline. The middle class, currently 34.3 percent of the population, is growing rapidly and is projected to replace the vulnerable as the largest economic group in LAC by 2016. The Southern Cone region (including Brazil) continued to be the most dynamic region and the main driver of poverty reduction in LAC, while poverty in Central America and Mexico proved more stubborn. About 68 percent of poverty reduction between 2003 and 2012 was driven by economic growth, with the remaining 32 percent arising from decline in inequality. Overall, equality of access to basic childhood goods and services has improved in recent years. Yet access can be further improved, and serious issues remain concerning the quality of those goods and services, particularly in education and housing infrastructure. Moreover, access increases with parental education and income or assets, reflecting low intergenerational mobility in many countries in the region. As with poverty reduction, most of the progress in equality of access since 2000 has come in the Southern Cone and the Andean regions, while many of Central America's countries managed only small improvements. There are also severe differences at the subnational level and between urban and rural areas, highlighting the need to strengthen the capacity of local governments to deliver high quality basic services to all their citizens.